Nosacīta atbrīvošana no kriminālatbildības - Voronoviča, Irina (Latvijas Universitāte, 2012)
Maģistra darbā izpētīta nosacīta atbrīvošana no kriminālatbildības, kā viens no vienkāršotiem procesa veidiem Latvijā. Pētījumā analizēts nosacītas atbrīvošanas no kriminālatbildības tiesiskais regulējums, pastāvošie priekšnoteikumi, tā piemērošanas nosacījumi, veikts salīdzinājums ar ārvalstīm. Darba gaitā analizēta šī institūta saturs un būtība, ievērojamas problēmas praksē. Norādīts uz nosacītas atbrīvošanas no kriminālatbildības pozitīvām pusēm, kā arī konstatēti šī institūta trūkumi. Autore izteica savus priekšlikumus tiesību normu pilnveidošanā. Nosacītas atbrīvošanas no kriminālatbildības socioloģiskais novērtējums norādīja uz tiesību normu neefektivitāti, kas liecina uz nosacītu atbrīvošanu no kriminālatbildības tālākveidošanu.

In the Master's Thesis discharge from criminal liability within putting the person on probation as one of the simplest types of the process in Latvia has been investigated. In the research the legal regulation of discharge from criminal liability within putting the person on probation, conditions of application thereof have been analyzed and a comparison with other states has been made. In the course of the work the content and the essence of this institution as well as significant problems in application thereof have been analyzed. The positive points as well as the flaws of discharge from criminal liability within putting the person on probation have been specified. The author has made suggestions for improvement of the legal regulations. Sociologic evaluation of discharge from criminal liability within putting the person on probation indicated inefficiency of legal regulations which means that further improvement to discharge from criminal liability within putting the person on probation is required.
Discharge from criminal liability within putting the person on probation
Keywords: Juridiskā zinātne